Functional Outcomes After Surgery for Total Colonic, Long-Segment, Versus Rectosigmoid Segment Hirschsprung Disease. Issue 3 (12th March 2022) - Verkuijl, Sanne J.; Meinds, Rob J.; van der Steeg, Alida F.W.; van Gemert, Wim G.; de Blaauw, Ivo; Witvliet, Marieke J.; Sloots, Cornelius E.J.; van Heurn, Ernst; Vermeulen, Karin M.; Trzpis, Monika; Broens, Paul M.A.
ABSTRACT: Objectives: Knowledge on long-term outcomes in patients with Hirschsprung disease is progressing. Nevertheless, differences in outcomes according to aganglionic lengths are unclear. We compared long-term bowel function and generic quality of life in Hirschsprung patients with total colonic or long-segment versus rectosigmoid aganglionosis. Methods: In this nationwide, cross-sectional study participants with proven Hirschsprung disease received the Defecation and Fecal Continence questionnaire, and the Child Health Questionnaire Child Form-87, or the WHO Quality of Life-100. We excluded deceased patients, patients who were younger than 8 years, lived abroad, had a permanent enterostomy, or were intellectually impaired. Results: The study population ( n = 334) was operated for rectosigmoid (83.9%), long-segment (8.7%), or total colonic aganglionosis (7.5%). Fecal incontinence in general was not significantly different between the three groups, but liquid fecal incontinence was significantly associated with total colonic aganglionosis (odds ratio [OR] = 6.00, 95% confidence interval [CI] 2.07–17.38, P  = 0.001). Regarding constipation, patients with total colonic or long-segment aganglionosis were less likely to suffer from constipation than the rectosigmoid group (OR = 0.21, 95% CI, 0.05–0.91, P  = 0.038 and OR = 0.11, 95% CI, 0.01–0.83, P  = 0.032). Quality of life was comparable between the three groups, except for a lower physical score in children with total colonic aganglionosis ( P  = 0.016). Conclusions: Over time Hirschsprung patients with total colonic or long-segment aganglionosis do not suffer from worse fecal incontinence in general. A difference in stool consistency may underlie the association between liquid fecal incontinence and total colonic aganglionosis and constipation in patients with rectosigmoid aganglionosis. Despite these differences, generic quality of life is comparable on reaching adulthood.